Surface-Enhanced Raman Scattering as an Emerging Characterization and Detection Technique - Mustafa Culha; Brian Cullum; Nickolay Lavrik; Charles K. Klutse (Journal of Nanotechnology)
While surface-enhanced Raman spectroscopy (SERS) has been attracting a continuously increasing interest of scientific community since its discovery, it has enjoyed a particularly rapid growth in the last decade. Most notable recent advances in SERS include novel technological approaches to SERS substrates and innovative applications of SERS in medicine and molecular biology. While a number of excellent reviews devoted to SERS appeared in the literature over the last two decades, we will focus this paper more specifically on several promising trends that have been highlighted less frequently. In particular, we will briefly overview strategies in designing and fabricating SERS substrates using deterministic patterning and then cover most recent biological applications of SERS.